A customized floating-point processor design for FPGA and ASIC based thermal compensation in high-precision sensing - Sajjad, M. (International Association for Educators and Researchers (IAER), 2021)
There are many types of sensors which require large dynamic range as well as high accuracy at the same time. Barometric altimeter is an example of such sensors. The signal processing techniques in the sensors are normally implemented using Field Programmable Gate Arrays (FPGAs) or Application-Specific Integrated Circuits (ASICs). The sensing variable in such type of the sensors is unwantedly environment dependent. So, for ensuring accuracy of the sensors this environmental dependency is minimized using the modeling and compensation techniques. In this work we have proposed a digital architecture for a programmable high precision computational unit which can be implemented in the FPGA or ASIC running the sensing algorithm of the sensors. This architecture can be used to implement polynomial compensation and it also supports reading and writing of the corresponding calibration coefficients even after the development of the sensors. Moreover, the architecture is platform independent. The architecture have been simulated for different FPGAs and ASIC and it has fulfilled the speed, accuracy and programmability requirements of the type of the sensors. The architecture has also been implemented and verified in a prototype of the barometric pressure sensor on Spartan-6 FPGA. Â© 2020 by the author(s).